5.9.4 Problems 301 to 400

Table 5.635: First order ode linear in derivative

#

ODE

Mathematica

Maple

759

\[ {}2 x +3 y+\left (2 y+3 x \right ) y^{\prime } = 0 \]

760

\[ {}4 x -y+\left (6 y-x \right ) y^{\prime } = 0 \]

761

\[ {}3 x^{2}+2 y^{2}+\left (4 x y+6 y^{2}\right ) y^{\prime } = 0 \]

762

\[ {}2 x y^{2}+3 x^{2}+\left (2 x^{2} y+4 y^{3}\right ) y^{\prime } = 0 \]

763

\[ {}x^{3}+\frac {y}{x}+\left (y^{2}+\ln \left (x \right )\right ) y^{\prime } = 0 \]

764

\[ {}1+y \,{\mathrm e}^{x y}+\left (2 y+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0 \]

765

\[ {}\cos \left (x \right )+\ln \left (y\right )+\left (\frac {x}{y}+{\mathrm e}^{y}\right ) y^{\prime } = 0 \]

766

\[ {}x +\arctan \left (y\right )+\frac {\left (x +y\right ) y^{\prime }}{1+y^{2}} = 0 \]

767

\[ {}3 x^{2} y^{3}+y^{4}+\left (3 y^{2} x^{3}+y^{4}+4 x y^{3}\right ) y^{\prime } = 0 \]

768

\[ {}{\mathrm e}^{x} \sin \left (y\right )+\tan \left (y\right )+\left ({\mathrm e}^{x} \cos \left (y\right )+x \sec \left (y\right )^{2}\right ) y^{\prime } = 0 \]

769

\[ {}\frac {2 x}{y}-\frac {3 y^{2}}{x^{4}}+\left (\frac {2 y}{x^{3}}-\frac {x^{2}}{y^{2}}+\frac {1}{\sqrt {y}}\right ) y^{\prime } = 0 \]

770

\[ {}\frac {2 x^{{5}/{2}}-3 y^{{5}/{3}}}{2 x^{{5}/{2}} y^{{2}/{3}}}+\frac {\left (3 y^{{5}/{3}}-2 x^{{5}/{2}}\right ) y^{\prime }}{3 x^{{3}/{2}} y^{{5}/{3}}} = 0 \]

771

\[ {}x^{3}+3 y-x y^{\prime } = 0 \]

772

\[ {}x y^{2}+3 y^{2}-x^{2} y^{\prime } = 0 \]

773

\[ {}x y+y^{2}-x^{2} y^{\prime } = 0 \]

774

\[ {}2 x y^{3}+{\mathrm e}^{x}+\left (3 x^{2} y^{2}+\sin \left (y\right )\right ) y^{\prime } = 0 \]

775

\[ {}3 y+x^{4} y^{\prime } = 2 x y \]

776

\[ {}2 x y^{2}+x^{2} y^{\prime } = y^{2} \]

777

\[ {}2 x^{2} y+x^{3} y^{\prime } = 1 \]

778

\[ {}x^{2} y^{\prime }+2 x y = y^{2} \]

779

\[ {}x y^{\prime }+2 y = 6 x^{2} \sqrt {y} \]

780

\[ {}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{2} \]

781

\[ {}x^{2} y^{\prime } = x y+3 y^{2} \]

782

\[ {}6 x y^{3}+2 y^{4}+\left (9 x^{2} y^{2}+8 x y^{3}\right ) y^{\prime } = 0 \]

783

\[ {}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{4} \]

784

\[ {}x^{3} y^{\prime } = x^{2} y-y^{3} \]

785

\[ {}y^{\prime }+3 y = 3 x^{2} {\mathrm e}^{-3 x} \]

786

\[ {}y^{\prime } = y^{2}-2 x y+x^{2} \]

787

\[ {}{\mathrm e}^{x}+y \,{\mathrm e}^{x y}+\left ({\mathrm e}^{y}+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0 \]

788

\[ {}2 x^{2} y-x^{3} y^{\prime } = y^{3} \]

789

\[ {}3 x^{5} y^{2}+x^{3} y^{\prime } = 2 y^{2} \]

790

\[ {}x y^{\prime }+3 y = \frac {3}{x^{{3}/{2}}} \]

791

\[ {}\left (x^{2}-1\right ) y^{\prime }+\left (x -1\right ) y = 1 \]

792

\[ {}x y^{\prime } = 6 y+12 x^{4} y^{{2}/{3}} \]

793

\[ {}{\mathrm e}^{y}+y \cos \left (x \right )+\left (x \,{\mathrm e}^{y}+\sin \left (x \right )\right ) y^{\prime } = 0 \]

794

\[ {}9 x^{2} y^{2}+x^{{3}/{2}} y^{\prime } = y^{2} \]

795

\[ {}2 y+\left (1+x \right ) y^{\prime } = 3+3 x \]

796

\[ {}9 \sqrt {x}\, y^{{4}/{3}}-12 x^{{1}/{5}} y^{{3}/{2}}+\left (8 x^{{3}/{2}} y^{{1}/{3}}-15 x^{{6}/{5}} \sqrt {y}\right ) y^{\prime } = 0 \]

797

\[ {}3 y+y^{4} x^{3}+3 x y^{\prime } = 0 \]

798

\[ {}x y^{\prime }+y = 2 \,{\mathrm e}^{2 x} \]

799

\[ {}\left (2 x +1\right ) y^{\prime }+y = \left (2 x +1\right )^{{3}/{2}} \]

800

\[ {}y^{\prime } = 3 \left (y+7\right ) x^{2} \]

801

\[ {}y^{\prime } = 3 \left (y+7\right ) x^{2} \]

802

\[ {}y^{\prime } = x y^{3}-x y \]

803

\[ {}y^{\prime } = \frac {-3 x^{2}-2 y^{2}}{4 x y} \]

804

\[ {}y^{\prime } = \frac {3 y+x}{-3 x +y} \]

805

\[ {}y^{\prime } = \frac {2 x y+2 x}{x^{2}+1} \]

806

\[ {}y^{\prime } = \cot \left (x \right ) \left (\sqrt {y}-y\right ) \]

1065

\[ {}y^{\prime } = 1+y^{2} \]

1098

\[ {}3 y+y^{\prime } = {\mathrm e}^{-2 t}+t \]

1099

\[ {}-2 y+y^{\prime } = {\mathrm e}^{2 t} t^{2} \]

1100

\[ {}y+y^{\prime } = 1+t \,{\mathrm e}^{-t} \]

1101

\[ {}\frac {y}{t}+y^{\prime } = 3 \cos \left (2 t \right ) \]

1102

\[ {}-2 y+y^{\prime } = 3 \,{\mathrm e}^{t} \]

1103

\[ {}2 y+t y^{\prime } = \sin \left (t \right ) \]

1104

\[ {}2 t y+y^{\prime } = 2 t \,{\mathrm e}^{-t^{2}} \]

1105

\[ {}4 t y+\left (t^{2}+1\right ) y^{\prime } = \frac {1}{\left (t^{2}+1\right )^{2}} \]

1106

\[ {}y+2 y^{\prime } = 3 t \]

1107

\[ {}-y+t y^{\prime } = t^{2} {\mathrm e}^{-t} \]

1108

\[ {}y+y^{\prime } = 5 \sin \left (2 t \right ) \]

1109

\[ {}y+2 y^{\prime } = 3 t^{2} \]

1110

\[ {}-y+y^{\prime } = 2 t \,{\mathrm e}^{2 t} \]

1111

\[ {}2 y+y^{\prime } = t \,{\mathrm e}^{-2 t} \]

1112

\[ {}2 y+t y^{\prime } = t^{2}-t +1 \]

1113

\[ {}\frac {2 y}{t}+y^{\prime } = \frac {\cos \left (t \right )}{t^{2}} \]

1114

\[ {}-2 y+y^{\prime } = {\mathrm e}^{2 t} \]

1115

\[ {}2 y+t y^{\prime } = \sin \left (t \right ) \]

1116

\[ {}4 t^{2} y+t^{3} y^{\prime } = {\mathrm e}^{-t} \]

1117

\[ {}\left (t +1\right ) y+t y^{\prime } = t \]

1118

\[ {}-\frac {y}{2}+y^{\prime } = 2 \cos \left (t \right ) \]

1119

\[ {}-y+2 y^{\prime } = {\mathrm e}^{\frac {t}{3}} \]

1120

\[ {}-2 y+3 y^{\prime } = {\mathrm e}^{-\frac {\pi t}{2}} \]

1121

\[ {}\left (t +1\right ) y+t y^{\prime } = 2 t \,{\mathrm e}^{-t} \]

1122

\[ {}2 y+t y^{\prime } = \frac {\sin \left (t \right )}{t} \]

1123

\[ {}\cos \left (t \right ) y+\sin \left (t \right ) y^{\prime } = {\mathrm e}^{t} \]

1124

\[ {}\frac {y}{2}+y^{\prime } = 2 \cos \left (t \right ) \]

1125

\[ {}\frac {2 y}{3}+y^{\prime } = 1-\frac {t}{2} \]

1126

\[ {}\frac {y}{4}+y^{\prime } = 3+2 \cos \left (2 t \right ) \]

1127

\[ {}-y+y^{\prime } = 1+3 \sin \left (t \right ) \]

1128

\[ {}-\frac {3 y}{2}+y^{\prime } = 2 \,{\mathrm e}^{t}+3 t \]

1129

\[ {}y^{\prime } = \frac {x^{2}}{y} \]

1130

\[ {}y^{\prime } = \frac {x^{2}}{\left (x^{3}+1\right ) y} \]

1131

\[ {}y^{2} \sin \left (x \right )+y^{\prime } = 0 \]

1132

\[ {}y^{\prime } = \frac {3 x^{2}-1}{3+2 y} \]

1133

\[ {}y^{\prime } = \cos \left (x \right )^{2} \cos \left (2 y\right )^{2} \]

1134

\[ {}x y^{\prime } = \sqrt {1-y^{2}} \]

1135

\[ {}y^{\prime } = \frac {-{\mathrm e}^{-x}+x}{{\mathrm e}^{y}+x} \]

1136

\[ {}y^{\prime } = \frac {x^{2}}{1+y^{2}} \]

1137

\[ {}y^{\prime } = \left (1-2 x \right ) y^{2} \]

1138

\[ {}y^{\prime } = \frac {1-2 x}{y} \]

1139

\[ {}x +y y^{\prime } {\mathrm e}^{-x} = 0 \]

1140

\[ {}r^{\prime } = \frac {r^{2}}{x} \]

1141

\[ {}y^{\prime } = \frac {2 x}{y+x^{2} y} \]

1142

\[ {}y^{\prime } = \frac {x y^{2}}{\sqrt {x^{2}+1}} \]

1143

\[ {}y^{\prime } = \frac {2 x}{1+2 y} \]

1144

\[ {}y^{\prime } = \frac {x \left (x^{2}+1\right )}{4 y^{3}} \]

1145

\[ {}y^{\prime } = \frac {-{\mathrm e}^{x}+3 x^{2}}{-5+2 y} \]

1146

\[ {}y^{\prime } = \frac {{\mathrm e}^{-x}-{\mathrm e}^{x}}{3+4 y} \]

1147

\[ {}\sin \left (2 x \right )+\cos \left (3 y\right ) y^{\prime } = 0 \]

1148

\[ {}\sqrt {-x^{2}+1}\, y^{2} y^{\prime } = \arcsin \left (x \right ) \]